Accelerated wound healing efficacy of hyaluronic acid-coated silver nanoparticles loaded with vancomycin: preparation, in vitro characterization, optimization, and in vivo assessments - Esraa Taha; Samia A. Nour; Marwa S. Khattab; Aya M. Yassin; Naglaa A. AbdElkader; Mai M. El Taweel (Future Journal of Pharmaceutical Sciences)
Abstract Background Skin integrity is crucial for human body normal physiological homeostasis. Skin wound management is critical to prevent progressive infection, scarring, and many other problems that could develop if wounds are not optimally treated. In this work, hyaluronic acid-coated silver nanoparticles loaded with vancomycin were evaluated as a potent comprehensive system to cure and inhibit infections of skin wounds. Results In vitro testing of the prepared silver nanoparticles was carried out, assaying its particle size, polydispersity index, zeta potential, and UV absorbance. Silver nanoparticles were optimized by applying two-factor three-level full factorial design utilizing Design-Expert® software. The optimum system showed particle size 399.71 nm ± 8.4, − 60.31 mV ± 4.6 for zeta potential, and 3.74 silver UV absorbance. In vivo study on surgically induced wounds in dogs manifested that the optimum drug-loaded system significantly boosted the wound healing process compared to plain system, drug solution, or control group providing rapid and complete skin regeneration. This was evidenced by clinical observations which showed significantly higher percent wound contraction and complete epithelization. Also, histopathological examinations revealed organized collagen deposition in well-formed granulation tissue in the optimum drug-loaded system. Biochemical, and gene expression analysis showed significant up-regulation of growth factor-related markers namely; VEGF and TGF-ß, and immune-related markers specifically; CCR4 and CD4 + . Conclusions Thus, hyaluronic acid-coated silver nanoparticles loaded with vancomycin offer a very auspicious system for skin wound healing purposes. Graphical abstract